Plasma-liquid system with rotational gliding discharge with liquid electrode - Nedybaliuk, O.A.; Solomenko, O.V.; Martysh, E.V.; Fedirchyk, I.I. (Вопросы атомной науки и техники, 2014)
Plasma-liquid system based on rotational gliding discharge with one liquid electrode was developed. Emission spectra of plasma of rotational gliding discharge with one liquid electrode were investigated. Discovered effective mechanism of controlling non-isothermal level of plasma in dynamic plasma-liquid systems. Major mechanism of expulsion of metal anode material from plasma-liquid systems with rotational discharges was shown. Разработана плазменно-жидкостная система, в основе которой лежит вращательный скользящий разряд с одним жидким электродом. Исследованы спектры излучения плазмы вращательного скользящего разряда с одним жидким электродом. Обнаружен эффективный механизм контроля уровня неизотермичности плазмы в динамических плазменно-жидкостных системах. Показан основной механизм выноса материала металлического анода в плазменно-жидкостной системе с вращательным скользящим разрядом. Розроблено плазмово-рідинну систему, в основі якої лежить обертальний ковзний розряд з одним рідким електродом. Досліджено спектри випромінювання плазми обертального ковзного розряду з одним рідким електродом. Виявлено ефективний механізм контролю рівня неізотермічності плазми в динамічних плазмово-рідинних системах. Показано основний механізм виносу матеріалу металевого аноду в плазмово-рідинній системі з обертальним ковзним розрядом.